Angelo Calemme e Bernard Stiegler: dalla tecnologia scien-tifica alla nuova critica dell’economia politica - Toffoletto, Edoardo (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2022)
This paper intends to present Angelo Calemme’s reconstruction of the Marxian project of a Critical history of technology offered in his most recent book Dalla Rivoluzione scientifica alla Rivoluzione industriale. Sulle condizioni marxiane dello sviluppo scientifico-tecnico (Meltemi Press Srl, Milano pp. 444, € 28, ISBN 9788855195652). This book questions the antithetical dominant approaches in the field of the history and theory of science and technology, which are crystallised in an at least centennial debate on the either external or internal logics of the development of scientific theory. Calemme proposes us a refreshing perspective in order to address the following problems: what has been the function of the applied mathematics in the technical development that brought to the Industrial Revolution? Such sciences develop themselves according to a proper ideology-free internal logic, or do they proceed according to an external causality, and namely, the value theory that directs economic structures and modes of production? The questions at stake are paramount to attempt a new critique of political economy able to expose the most inner logics of contemporary algorithmic and cognitive capitalism. This overview of Calemme’s work argues that his proposal consists of a dialectical sublation of the debate through a genealogical understanding of Hegel’s (concept of work-labour) and Charles Darwin’s (concept of life) – among others – influence on Marx’s notes on the history of technology. Ultimately, one must dialectically understand the relation between Critical history of technology and Critique of political economy, hence opening a perspective that can be productively integrated with Bernard Stiegler’ sproject of a general organology. Marx; Darwin; Stiegler; Organology; Critical History of Technology; Critique of Political Economy.